2018
DOI: 10.1186/s12876-018-0820-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of clarithromycin resistance in Helicobacter pylori in Santiago, Chile, estimated by real-time PCR directly from gastric mucosa

Abstract: BackgroundCurrent available treatments for Helicobacter pylori eradication are chosen according to local clarithromycin and metronidazole resistance prevalence. The aim of this study was to estimate, by means of molecular methods, both clarithromycin and metronidazole resistance in gastric mucosa from patients infected with H.pylori.MethodsA total of 191 DNA samples were analyzed. DNA was purified from gastric mucosa obtained from patients who underwent an upper gastrointestinal endoscopy at an university hosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
1
9
1
1
Order By: Relevance
“…The qRT-PCR analysis of 50 biopsy specimens revealed an H. pylori infection incidence rate of 64%, which was higher than that in other studies, which reported H. pylori infection prevalence of 48.7% and 57% [19,20]. Previous studies in Saudi Arabia have reported that the H. pylori infection prevalence rates ranged from 28-70% with an average of 50% [21].…”
Section: Discussioncontrasting
confidence: 56%
“…The qRT-PCR analysis of 50 biopsy specimens revealed an H. pylori infection incidence rate of 64%, which was higher than that in other studies, which reported H. pylori infection prevalence of 48.7% and 57% [19,20]. Previous studies in Saudi Arabia have reported that the H. pylori infection prevalence rates ranged from 28-70% with an average of 50% [21].…”
Section: Discussioncontrasting
confidence: 56%
“…The specific reasons were: Pediatric population 19 ; Other Latin American population 14,34,35 ; study published before 2010 16,3739 ; reviews 14,35,38 ; duplicated sample and population from regions outside Santiago 36,37,39,40 . Two studies met the inclusion criteria 17,18 and were analyzed with our study, the combined sample size was 194 patients. PRISMA flow diagram is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, increasing of clarithromycin resistance could be expected due to its use in the treatment of extra-digestive infections (19) . Recently, Gonzalez-Hormazabal et al (20) estimated a 31.8% prevalence of clarithromycin resistance in H. pylori at Santiago-Chile by real-time PCR directly from gastric mucosa. These results are higher than the results presented in this work, but it is known that bacteriological cultures underestimate the prevalence of H. pylori as compared to other methods, especially as compared to PCR detection for clarithromycin.…”
Section: Discussionmentioning
confidence: 99%